Liver proteomic analysis of Bai-Hu-Tang treatment to systemic inflammatory response - Shidong Zhang; Shaoqiang Wei; Liu Sen (Pharmacological Research - Modern Chinese Medicine, 2024)
Introduction: Bai-Hu-Tang (BHT), a classical prescription of traditional Chinese medicine, has been extensively used to treat many infectious diseases and high fever syndrome. However, the specific mechanisms and molecular targets affected by BHT have not been thoroughly investigated in the context of treating systemic inflammatory response. This study aimed to explore the comprehensive protein mechanism of BHT during treatment of the lipopolysaccharide (LPS) systemic inflammatory response. Methods: The rabbit model of the systemic inflammatory response was established by LPS intravenous injection (15 μg/kg·bw), and aqueous extract of BHT was administrated by gavage to the model rabbits. At the same time, a group of normal rabbits were also gavaged with BHT alone. Based on liver histopathological study, total liver protein was extracted, and two-dimensional liquid chromatography (LC) - tandem mass spectrometry (MS) coupled with isobaric tags for relative and absolute quantification (iTRAQ) labeling analysis was employed to identify and quantify the liver proteome. Differentially expressed proteins (DEPs) were screened through comparing with control animals, and bioinformatics analysis was conducted to explore kyoto encyclopedia of genes and genomes (KEGG) pathways enrichment and protein clustering among different groups. Real time polymerase chain reaction (RT-PCR) was used to detect the mRNA expression levels of 4 ribosomal proteins to verify the proteomic results. Results: The results showed that ribosome biogenesis is the most significant biological process and ribosomal DEPs mainly distribute in the large subunit of ribosome during the BHT treatment to the LPS systemic inflammatory response. RT-PCR confirmed that BHT had an effect on mRNA expression of ribosome proteins. Discussion: Therefore, the biological pathway of ribosome biogenesis and the regulation of ribosomal proteins may be the cruicial factors when employing BHT for the treatment of the systemic inflammatory response induced by LPS.